For each pair of functions f and g
below, find f(g(x)) and g(f(x)).
Then, determine whether f and g
are inverses of each other.
(a) F(x)−one forth,x≠0, G(x)= one forthX, x≠0 F(g(x)),G(f(x))
(b) F(x)=x-3,G(x)=x+3,F(g(x)), G(f(x))
F and G are not inverses of each other
F (G(x))= f(x+3) =x+3-3=x
G(f(x))= G(x-3) =x-3+3=x
F and G are inverses of each other
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?